2018
DOI: 10.12688/wellcomeopenres.13181.3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of detecting potentially serious incidental findings during multi-modal imaging

Abstract: There are limited data on the impact of feedback of incidental

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…This pattern is biologically plausible and has been seen in data from primary studies. 21 25 26 28 53 The heterogeneity between included studies, relative rarity of potentially serious incidental findings, methods of meta-analyses, and conservative calculation of confidence intervals could have obscured true differences in the prevalence of potentially serious incidental findings between regions. Results on incidental findings from ongoing imaging studies based on large populations (including the UK Biobank imaging substudy, which by late October 2018 had imaged more than 30 000 of an intended 100 000 participants) should be able to confirm or refute this pattern in future.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern is biologically plausible and has been seen in data from primary studies. 21 25 26 28 53 The heterogeneity between included studies, relative rarity of potentially serious incidental findings, methods of meta-analyses, and conservative calculation of confidence intervals could have obscured true differences in the prevalence of potentially serious incidental findings between regions. Results on incidental findings from ongoing imaging studies based on large populations (including the UK Biobank imaging substudy, which by late October 2018 had imaged more than 30 000 of an intended 100 000 participants) should be able to confirm or refute this pattern in future.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, some contemporary research studies, such as All of Us (which aims to enroll 1 million or more diverse participants to enable research on a wide range of common and rare diseases) and Project Baseline (which involves deep health data collection in a longitudinal cohort of at least 10 000 participants to map human health and health transitions), are planning to return many individual research results in an effort to create value. 3 While most published experiences about the return of research results to study participants have demonstrated mixed benefits and risks and are limited to studies of returning genetic or imaging results, [4][5][6] little evidence is available to answer key questions: what results to return and when and how to return them (Box).…”
mentioning
confidence: 99%
“…Access to independently standardized and validated controls in a variety of matrices (plasma, serum, urine, etc) for established and emerging biomarkers would be a valuable resource for investigators and facilitate more consistent biomarker results between laboratories. This in turn supports the goals of improved data rigor and reproducibility, and the more ethical discussion regarding disclosure of validated data to study participants [2325].…”
Section: Discussionmentioning
confidence: 53%